Estudio sociolingüístico de la vitalidad del Kichwa en el Barrio Chuipe, Parroquía Punín, Cantón Riobamba - Tene Bastidas, Segundo Pedro (2018)
The present investigative work on the sociolinguistic study and case analysis emphasizes knowing the vitality and validity of the Kichwa language within a marginal urban context located in the Punin parish, Chimborazo province, in the same way seeks to know the attitude of the people in front of the indigenous language because this allows to determine the level of speech proficiency that the inhabitants of the sector have. The research is based on the bibliographic theories that allow to know in depth the subject of study, also the collection of information in the field within the community context makes it easier to know the interest of each one of the people, because this allows generating a revitalization proposal in order to contribute to the national context in strengthening and assessing the cultural elements and practices of the Kichwa people, especially their language. In the Chuipe Punín neighborhood there is a slight degree of bilingualism, since they dominate more the Castilian language for the connection with other cultures. The Kichwa is used within the neighborhood with little frequency, this means that the indigenous language remains in force but with high degrees of risk that tends to disappear, where we can state that it is due to the presence of several factors such as colonized education, emigration of the population mainly of the young people, the political proselytisms by the governments in turn, etc. In addition to this is because of the closures of bilingual and community intercultural educational institutions.